The Regulatory Mechanism of EpCAM N-Glycosylation-Mediated MAPK and PI3K/Akt Pathways on Epithelial-Mesenchymal Transition in Breast Cancer Cells: EpCAM N-Glycosylation and PI3K/Akt Pathways on Breast Cancer Cells - Wen, Ronglan; Lin, Hui; Li, Xiaohua; Lai, Xuedan; Yang, Fan (Cellular and Molecular Biology, 2022)
It was to investigate the regulation of motigen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) pathways mediated by epithelial cell adhesion molecules (EpCAM) N-glycosylation on epithelial-mesenchymal transition (EMT) in breast cancer cells. Breast cancer cells MCF-7 and MDA-MB-231 were taken in the control group; the blank vector plasmid transfection (blank plasmid group) and EpCAM N-glycosylation mutant plasmid transfection (Mutant-EpCAM group) were analyzed. The EpCAM in breast cancer cells was localized by immunofluorescence technique, the proliferation activity of cells in each group was detected by methyl thiazolyl tetrazolium (MTT) assay, and the clonality of cells was detected by plate cloning. and apoptosis-related proteins (Caspase-3, Bcl-2, and Bax), EMT-related molecular markers (E-cadherin, N-cadherin, and Vimentin), as well as MAPK and PI3K/Akt pathway-related proteins (p38, PI3K, and Akt) in cells were detected by western blotting (WB). EpCAM N-glycosylation mutations did not alter the expression localization of EpCAM in breast cancer cells. Compared with the control group and the blank plasmid group, the cell proliferation activity and the number of colonies formed were decreased in the Mutant-EpCAM group (P<0.05). The protein expressions of Caspase-3, Bax, and E-cadherin were up-regulated significantly, and the expressions of Bcl-2, N-cadherin, Vimentin, p-p38, p-PI3K, and p-Akt were greatly down-regulated (P<0.05). EpCAM N-glycosylation could regulate the EMT in breast cancer cells through MAPK and PI3K/Akt pathways.